Phosphatized early Cambrian archaeocyaths and small shelly fossils (SSFs) of southwestern Mongolia - Pruss, S; Dwyer, C; Smith, E; Macdonald, F; Tosca, N (Elsevier, 2017)
Archaeocyaths are an enigmatic group of calcifying sponges prevalent in early Cambrian (Terreneuvian to Series 2) successions around the world and preserved predominantly in reefal buildups, but also in adjacent reworked deposits. Here we report exceptionally preserved phosphatized archaeocyaths and small shelly fossils from phosphatized reef flank deposits at the top of the Salaagol Formation of southwestern Mongolia. Recent chemostratigraphic age models suggest that these archaeocyaths are among the earliest reported in the Terreneuvian Stage 2 (Tommotian). These fossils provide a window into the mechanisms of archaeocyath phosphatization, a generally rare mode of archaeocyath preservation. To assess the composition and nature of phosphatization, fossil assemblages were examined in insoluble residue and thin section. These archaeocyaths are preserved as phosphatic internal molds in residue, and both phosphatized and unphosphatized archaeocyaths are present in thin section. The occurrence of internal molds and complementary mineralogical data suggest that the decay of organic material within the archaeocyaths created the necessary redox conditions for apatite nucleation. We propose that, shortly after death, this assemblage was transported to a deeper water environment, and that the presence of organic matter in a low oxygen setting led to abundant phosphatization of archaeocyaths.